KORELASI ANTARA KADAR GULA DARAH DENGAN KUALITAS HIDUP PASIEN DIABETES MELLITUS DI FASILITAS PELAYANAN KESEHATAN PRIMER - Yumassik, Abdul Mahmud; Alfian, Riza; Riski, Akhmad; Soraya, Soraya; Ayu, Welinda Dyah; Rianto, Leonov; Eka Kumalasari (Jurnal Insan Farmasi Indonesia, 2022)
Diabetes mellitus is a metabolic symptom caused by an increase in blood glucose due to impaired insulin secretion, insulin resistance, or both. Blood glucose levels above the normal limit have an influence on the quality of life of diabetes mellitus patients. The study was conducted with a cross sectional design. Data collection was carried out prospectively during the period from May to June 2022. The sample in this study was patients with diabetes mellitus in one of the primary health care centers in Banjarmasin City. Quality of life data was collected using the EQ-5D questionnaire, while blood glucose levels data was obtained from medical record patient. A total of 75 samples participated in this study. The results showed that the mean fasting blood sugar level was 162,95 mg/dL. The mean value of the sample's quality of life score based on the EQ-5D index was 0,739. There is a significant correlation between blood glucose levels and the quality of life of patients with diabetes mellitus. The results of the correlation indicated that the lower the blood glucose level of patients with diabetes mellitus, the higher their quality of life.